The Role of Islamic Religious Education Teachers in Facing Digital Era Challenges: A Case Study at The Sekolah Indonesia Kuala Lumpur - Anjelina, Najwa; Khusnul Hamdani, Mohammad (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This article discusses the role and challenges of Islamic Religious Education (PAI) teachers in the digital era. This study aims to answer the question: What is the role of PAI teachers in teaching PAI in the digital era and the challenges faced in teaching PAI in the digital era? The method used is a qualitative approach with a case study at the Indonesian School of Kuala Lumpur. The study involved two informants, namely PAI teachers, and direct observation in the field with data triangulation techniques. The results of the study indicate that PAI teachers play a role as murabbi, mua'allim, and muaddib in guiding students to understand Islamic teachings, especially in the digital era. This study also emphasizes the importance of developing professional competence and cooperation between teachers, parents, and the community to fortify students with Islamic religious values. Adaptation to technology and relevant approaches is essential to creating a young generation that is intelligent and has noble character in the digital era.